Evaluation of Serum Calcium as a Predictor of Biochemical Recurrence following Salvage Radiation Therapy for Prostate Cancer. (31st March 2013) - Peterson, Jennifer L.; Buskirk, Steven J.; Heckman, Michael G.; Parker, Alexander S.; Diehl, Nancy N.; Tzou, Katherine S.; Paryani, Nitesh N.; Ko, Stephen J.; Daugherty, Larry C.; Vallow, Laura A.; Pisansky, Thomas M.
Abstract : Background . Previous reports have shown a positive association between serum calcium level and prostate cancer mortality. However, there is no data regarding whether higher serum calcium levels are associated with increased risk of biochemical recurrence (BCR) following salvage radiation therapy (SRT) for prostate cancer. Herein, we evaluate the association between pretreatment serum calcium levels and BCR in a cohort of men who underwent SRT. Methods . We evaluated 165 patients who underwent SRT at our institution. Median dose was 65.0 Gy (range: 54.0–72.4 Gy). We considered serum calcium as both a continuous variable and a 3-level categorical variable (low [≤9.0 mg/dL], moderate [>9.0 mg/dL and ≤9.35 mg/dL], and high [>9.35 mg/dL]) based on sample tertiles. Results . We observed no evidence of a linear association between serum calcium and BCR (relative risk (RR): 0.96, P = 0.76 ). Compared to men with low calcium, there was no significantly increased risk of BCR for men with moderate (RR: 0.94, P = 0.79 ) or high (RR: 1.08, P = 0.76 ) serum calcium levels. Adjustment for clinical, pathological, and SRT characteristics in multivariable analyses did not alter these findings. Conclusion . Our results provide evidence that pretreatment serum calcium is unlikely to be a useful tool in predicting BCR risk following SRT.